To the Question How the “Iron Dogs” of the Batuids Broke down the “Golden Yurt” of Their “Masters - Grinberg M. (Золотоордынское обозрение)
Research objective: As the ruler of the Golden Horde from 1361 to 1362, Khidr became the first khan to represent the Shibanid dynasty, while all previous representatives of this dynasty remained loyal to the Batuids until he came to power. This situation forms one of the key moments of the initial period of the “Great Troubles”. This article is devoted to the circumstances and consequences of the ascension and the short-term rule of this Khan in the Golden Horde. In addition, the goal here is to highlight the role and interests of the high hereditary metropolitan and regional aristocracy in these events. Research materials: Since, as a result of the latest research, Chinggis-nama is recognized as a source that preserves historical facts, rather than merely folk elements as was previously thought, it is necessary to involve Ötemish Hajji’s work in covering those historical events and processes where it contains a unique information regarding them. At the same time, because it is still difficult to distinguish between the factual and the mythological elements of its content, verification of Chinggis-nama’s information with information from other sources (as well as from archaeology, numismatics, and other auxiliary historical disciplines) is required when possible. So, the main source used in the article is the historical Chinggis-nama of Ötemish Hajji. Additional sources are Russian chronicles, Tawarikh-i guzida-i Nusrat-nama, Muntakhab al-tawarikh-i Muini by Muin al-Din Natanzi, a Venetian source by Benedetto Bianco which was very recently introduced into scholarly circulation, and others. Results and novelty of the research: This article is one of the first studies, using the account of Ötemish Hajji as a main historical source for analysing and reconstructing a real historical event (namely, the seizure of power by the Shibanids in the Golden Horde in 1360) and its consequences. It is proposed to continue to involve this source in the study of historical events, but with great caution. Regarding the stated topic, the author of the present article dares to hope that the results of such work bring new and significant contribution to the research of this rather poorly studied period in the history of the Ulus of Jochi. Especially, the results help to reveal and emphasize the causes and circumstances that led the Golden Horde into a period of great turmoil, i.e., the “Great Troubles”.